2005
DOI: 10.1017/s0265021503000577
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sevoflurane on the ex vivo secretion of TNF-α during and after coronary artery bypass surgery

Abstract: Sevoflurane reduces production of TNF-alpha more than total intravenous anaesthesia with midazolam-sufentanil during cardiac surgery. This may reduce cardiac morbidity and the length of stay in the intensive care unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
7
0
3
Order By: Relevance
“…It has a low blood/gas partition coefficient and the advantages of anesthesia induction, quick recovery and hemodynamic stability. Sevoflurane has anti-inflammatory properties, and pretreatment with sevoflurane can protect lung tissue from ischemia–reperfusion injury, 2 , 3 but the mechanism of its protective effect on reperfusion injury is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…It has a low blood/gas partition coefficient and the advantages of anesthesia induction, quick recovery and hemodynamic stability. Sevoflurane has anti-inflammatory properties, and pretreatment with sevoflurane can protect lung tissue from ischemia–reperfusion injury, 2 , 3 but the mechanism of its protective effect on reperfusion injury is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…There are several significant advantages of continuous measurements of systemic inflammation during CPB as compared with conventional techniques that will be useful to the physicians. First, pharmacological agent selection including anesthetic drugs, in conjunction with different modes of perfusion has significant effects on systemic inflammation , and continuous monitoring of inflammatory biomarkers will benefit several ongoing surgical studies of the immune response to the use of certain anesthetic agents and anti‐inflammatory steroids. Online measurements would permit a study of the effects of different pharmacological agents and provide indications for intraoperative substitution of agents.…”
Section: Resultsmentioning
confidence: 99%
“…The cardioprotective effects of a volatile anesthetic regimen during CABG were confirmed in other reports that used different anesthetic and surgical protocols, and in patients undergoing off-pump CABG. 46 53 These clinical studies clearly indicate that volatile anesthetics protect the myocardium during CABG. However, another study in patients undergoing off-pump CABG observed no significant difference in the incidence of myocardial ischemia.…”
Section: Does Choice Of Anesthetic Regimen Matter In Clinical Practice?mentioning
confidence: 85%